A decision support system for debris-flow hazard mitigation in towns based on numerical simulation: a case study at Dongchuan, Yunnan Province. (30th June 2008) - Wei, Fangqiang; Hu, Kaiheng; Cui, Peng; Guan, Qun
The hazard mitigation decision support system is an efficient method to avoid severe human damage by debris flow. Using modern technology, the multi-functional synthetical mitigation decision support system integrates debris flow monitoring, information transmission, disaster forecast and alarm, disaster estimate, evacuation and rescue plan to provide support for making mitigation strategic decision in all aspects before and after the disaster. The system was successfully utilised in debris flow hazard mitigation in the Dongchuan suburb in Yunnan Province. According to the data of monitoring and predicting, the system can simulate the movement of debris flow, and define the range and hazard zone of debris flow disaster. The result can be used to conduct disaster estimation, and prepare evacuation and rescue plan, which increases the degree of disaster mitigation.